2021
DOI: 10.2147/rmhp.s317849
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Healthcare Services for People with Physical Disabilities in Hawassa City Administration, Ethiopia: A Cross-Sectional Study

Abstract: Background Persons with disabilities experience significant barriers to accessing health care. These barriers may be more serious in countries such as Ethiopia. In this study, we aimed to assess the prevalence of accessibility and associated factors among physically disabled people visiting physical disability associations in Hawassa. Methods A cross-sectional study was conducted among 345 randomly selected physically disabled people who visited disability associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, they have reported that the health care providers treated them without discrimination and are supportive. This study was supported by the study conducted among people with physical disabilities in Hawassa 22 that PWDs have limited access to health care. This may be because people with disabilities require specific access to healthcare due to their restrictions.…”
Section: Discussionmentioning
confidence: 71%
“…However, they have reported that the health care providers treated them without discrimination and are supportive. This study was supported by the study conducted among people with physical disabilities in Hawassa 22 that PWDs have limited access to health care. This may be because people with disabilities require specific access to healthcare due to their restrictions.…”
Section: Discussionmentioning
confidence: 71%
“…In study by Tesfaye et al in Hawassa confirm that accessibility to healthcare services among people with disabilities was poor [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to out of pocket indirect costs, which greatly hinder access to healthcare services. Another important barrier to accessing healthcare among people with disabilities is the higher outof-pocket expenditure (OoPE) due to the higher cost of services (Tesfaye et al 2021). Disability is positively associated with higher OoPE (Sriram and Khan 2020).…”
Section: Physical and Financial Barriersmentioning
confidence: 99%
“…A systematic review concluded that the prevalence of type 2 diabetes is high among people with disabilities (Thiagesan et al 2022). They face various barriers while accessing health services such as lack of disability-friendly transport, communication barriers, inability to access the health facility, and lack of disability-friendly equipment such as beds, chairs, and stretchers (Tesfaye et al 2021). The intersectionality of age and gender, age-gender-caste, and gender-caste-disability adds to the burden and vulnerability of disability (Sharma and Sivakami 2019).…”
Section: Introductionmentioning
confidence: 99%